Antibacterial Potential of Novel Poly-Herbal Bio-Disinfectant - Pawar, Devkirani Pandharinath; Jadhav, Mahadev A; Wadmare, Durga Ishwar; Hiwale, Rani Baban (Journal for Research in Applied Sciences and Biotechnology, 2024)
Indigenous medicinal plants like Azadirachta Indica, Mentha, Ocimum Tenuiflorum, Phyllanthus emblica and Aloe vera is traditionally used for treating different ailments in India. It is considered as safe medicinal plants and modulates the numerous biological processes without any adverse effect. It is a vital principle in the prevention control, and reduction of any acquired infection. We aim to present the herbal preparation for human health hazard free bio disinfectant. Indigenous medicinal plants with reported effective results against Escherichia coli, Staphylococcus aureus, Serratia marcescens, Bacillus, Pseudomonas aeruginosa, Salmonella typhi along with least toxic impact on environment. The antimicrobial activities by agar well diffusion indicated by zone of inhibition were resulted against Escherichia coli (24 mm), Staphylococcus aureus (10 mm), Serratia marcescens (11 mm), Bacillus (20 mm), Pseudomonas aeruginosa (22mm), Salmonella typhi (15 mm). The highest potential was observed in methanolic extract as compared to aqueous extract with even concentration. The use of medicinal plants extracts in bio disinfectant spray is mainly due to the anti-allergic, antioxidant, antibacterial, antifungal, antiviral, and anti-inflammatory properties are present. The antioxidant activity was linearly proportional to the concentration and the result showed that the antioxidant activity of all the extracts was found to increase in concentration with increased absorbance of the reaction mixture indicates increase in antioxidant activity. The formulation was evaluated for its physical parameters. It is sure that these ingredients on combination behave as an effective bio-disinfectant product. It can be used as a gel, liquid, spray on medical device and it also plays an important role in the production of various types of disinfectant products. Natural herbal bio disinfectants are affordable, effective and environmentally friendly.